Comparison of susceptibility of HIV-1 variants to antiretroviral drugs by genotypic and recombinant virus phenotypic analyses. (August 2015) - Chang, Shuai; Zhuang, Daomin; Li, Jingyun; Liu, Siyang; Li, Hanping; Han, Jingwan; Li, Lin; Liu, Yongjian; Bao, Zuoyi; Li, Tianyi; Song, Hongbin; Zhang, Wenfu
Highlights: Phenotypic susceptibilities to six antiretroviral drugs were measured using a high-throughput, multi-cycle, recombinant virus phenotypic assay. For most cases, the genotypic and in-house recombinant virus phenotypic analyses yielded similar results, with a concordance rate of 84.2%. The cut-off intervals for HIV-1 antiretroviral drugs may be extended to some extent. The disparity in HIV-1 susceptibility poses a need to invest the clinical outcome of antiretroviral therapy of special individuals. Summary: Objective: This study utilized genotypic and in-house recombinant virus phenotypic assays to examine HIV-1 variant susceptibility to antiretroviral (ARV) drugs; comparisons were made between the analyses. Methods: A nested PCR was employed to amplify the HIV-1 gag-pol gene, which comprised the entire PR gene (codons 1–99) and the former RT gene (codons 1–312). Genetic resistance was determined by submitting the sequences to the Stanford University Network HIV-1 Database. Phenotypic susceptibilities to six ARV drugs were measured using a high-throughput, multi-cycle, recombinant virus phenotypic assay. Results were expressed in terms of the IC50 (half maximal inhibitory concentration) and fold-change values. The relationship between phenotypic drug resistance and genetic polymorphisms was determined. Results: Nineteen fragment sequences for which recombinant viruses were successfully constructed were translated and compared with the consensus B sequences in the Stanford University Network HIV-1 Database. No recognizable genotypic resistance-associated mutations were noted, except in one sample. Each homologous replication-competent recombinant viral fold-change in the presence of six ARV drugs used widely in China was measured. According to the clinical and statistical criteria, 16 of the 19 samples were susceptible to the six drugs tested. The majority of phenotypic and genotypic results obtained were in agreement, with a concordance rate of 97.4%. Both phenotypic and genotypic assays suggested that sample HN2009001 was resistant to all drugs tested. All phenotypic and genotypic results obtained regarding the susceptibility of the 19 recombinant viruses to nucleoside reverse transcriptase inhibitors (NRTIs) were in agreement. With regard to the genotypic results for the non-nucleoside reverse transcriptase inhibitors (NNRTIs), 7.9% (3/38) were inconsistent with the phenotypic results. Conclusions: The in-house recombinant virus phenotypic assay was able to provide a straightforward quantitative assessment of resistance. In most cases, the genotypic and novel phenotypic assays yielded similar results. The disparity in HIV-1 susceptibility indicates a need to further investigate the clinical outcomes of antiretroviral therapy in certain individuals.